Specific features of the course of duodenal ulcer in bronchial asthma (clinical and pathomorphological aspects) - G M Chernyavskaya; R I Pleshko; E I Beloborodova; I V Sukhodolo; E V Plekhanova (Терапевтический архив, 2004)
Aim. To study incidence of gastroduodenal ulcer (GDU) in bronchial asthma and clinicomorphological features of ulcer disease in BA in long-term use of systemic corticosteroids (SCS) and without SCS. Material and methods. The trial covered 297 BA patients. They have undergone clinicoendoscopic examination of the gastroduodenal zone (GDZ) for duodenal ulcer with assessment of clinical gastroenterological symptoms and morphological analysis of bipsies of gastric and duodenal mucosa using histological, histochemical and morphometric methods. Results. BA patients were found to have high incidence of duodenal ulcer (21.9%). Morphologically, they had active immune inflammation with hyperergic component. The results of the study did not confirm the opinion about a key role of SCS in development of GDU in BA. Small doses of SCS in patients with BA and GDU do not deteriorate ulcerogenesis. Conclusion. One of the factors determining combination of ulcer disease with В A may be chronic hyperergic inflammation of GDZ mucosa stimulating realization of predisposition to ulcer and its chronic recurrent course.